4-Aminopyridine Induced Activity Rescues Hypoexcitable Motor Neurons from Amyotrophic Lateral Sclerosis Patient-Derived Induced Pluripotent Stem Cells. (28th March 2016) - Naujock, Maximilian; Stanslowsky, Nancy; Bufler, Sebastian; Naumann, Marcel; Reinhardt, Peter; Sterneckert, Jared; Kefalakes, Ekaterini; Kassebaum, Carola; Bursch, Franziska; Lojewski, Xenia; Storch, Alexander; Frickenhaus, Marie; et al.
Abstract: Despite decades of research on amyotrophic lateral sclerosis (ALS), there is only one approved drug, which minimally extends patient survival. Here, we investigated pathophysiological mechanisms underlying ALS using motor neurons (MNs) differentiated from induced pluripotent stem cells (iPSCs) derived from ALS patients carrying mutations in FUS or SOD1 . Patient-derived MNs were less active and excitable compared to healthy controls, due to reduced Na + /K + ratios in both ALS groups accompanied by elevated potassium channel ( FUS ) and attenuated sodium channel expression levels ( FUS, SOD1 ). ALS iPSC-derived MNs showed elevated endoplasmic reticulum stress (ER) levels and increased caspase activation. Treatment with the FDA approved drug 4-Aminopyridine (4AP) restored ion-channel imbalances, increased neuronal activity levels and decreased ER stress and caspase activation. This study provides novel pathophysiological data, including a mechanistic explanation for the observed hypoexcitability in patient-derived MNs and a new therapeutic strategy to provide neuroprotection in MNs affected by ALS.